Immunomodulatory Effects of Phosphorylated Radix Cyathulae officinalis Polysaccharides in Immunosuppressed Mice - Haibo Feng; Jing Fan; Lang Lin; Yunjie Liu; Dongkun Chai; Jie Yang (Molecules, 2019)
This research aimed to investigate the immunomodulatory effects of phosphorylated Radix Cyathulae officinalis Kuan polysaccharides (pRCPS) in immunosuppressed mice, improving their cellular and humoral immune function. Our results showed that pRCPS increased serum immunoglobulin (IgG, IgA, IgM) concentrations significantly, enhanced splenocyte proliferation, and the thymus and spleen indices. pRCPS also promoted phagocytosis in peritoneal macrophages and enhanced cytokine (IFN-γ, IL-2, -4, -5, -6, and -10) serum levels. Importantly, pRCPS increased the proportions of selected T cell subpopulations (CD3+, CD4+, and the CD4+ to CD8+ ratio). Our results revealed that phosphorylation of the polysaccharides promoted their immune-enhancing effects. Thus, pRCPS can enhance cellular and humoral immunity and could be used as an immune-enhancing agent to overcome cyclophosphamide (CY)-induced immunosuppression.